The legality of Euthanasia from the Malaysian and Islamic perspectives - Alias, Fadhlina; Muhammad, Mizan; Jahn Kassim, Puteri Nemie (2014)
The subject of euthanasia has generated many controversial debates, particularly on its legality. This has been primarily due to the doctrine of sanctity of life which is a predominant principle in many religions and embedded in moral values. The underlying precept is that human life is sacred and demands respect as all life comes from God and life can only be taken away intentionally through due process of law. Thus, ending a person’s life even upon his or her request is considered in many jurisdictions as a criminal offence. Irrespective of humanitarian motives, a doctor who aids a patient in this act will be in breach of his unequivocal duty as a doctor and considered to have committed an unlawful act which will subject him to legal sanctions. Countries such as the United Kingdom, Australia, New Zealand and Turkey have explicit legal provisions banning, in particular, active euthanasia, while countries such as the Netherlands, Belgium, Switzerland and certain states in the U.S have taken positive steps to legalise euthanasia in certain aspects. The ethical codes and laws in Malaysia have yet to develop to the fullest extent in dealing with these issues. Although Malaysian statutory legislation contain express provisions banning active euthanasia, the legal position on passive euthanasia remains implicit. In the absence of indicative legal provisions and judicial precedents governing certain matters arising, it has been the practice of the Malaysian courts to refer to relevant legal principles inherent in English cases. The Islamic perspective is also an important and influential factor in the development of the legal framework in Malaysia as a whole, due to the fact that Islam is proclaimed as the country’s official religion. Thus, there is a need for the existence of a clear and comprehensive regulatory framework governing the legality of euthanasia in Malaysia.